Synthesis, characterization and biological activity of some carbazone Schiff bases and their metal complexes / Mohd. Rizal bin Razali - Razali, Mohd. Rizal (2009)
All the metal complexes in this study are synthesized by the general method which the ligand was first prepared by refluxing the precursors of the Schiff base. It was then followed by the addition of the appropriate metal salt to form metal complexes. The characterization of the series of the Schiff base complexes of Ni(II), Cu(II), Zn(II) and Cd(II) with ligand systems containing nitrogen, sulphur and oxygen donor atoms were also carried out. Formation of the Schiff base ligands were confirmed by the presence of v(C=N) band at the range 1550-1650 cm-1 in the IR spectra. In some cases the absence of a band around 1700 cm-1 that can be attributed to C=O stretching indicates the complete condensation of the carbonyl group. The reductions in the relative intensity of the thione sulphur and keto oxygen bands were evidence of the complexation. The 1H and 13C NMR spectroscopy technique was employed to prove the formation of the Schiff base ligands. The electronic spectra of metal complexes with Schiff bases containing several donors atom displayed charge transfer at the range of 26000-30000 cm-1. In the case of Ni(II) ad Cu(II) complexes, low intense visible bands were seen between 17000-20000 cm-1. Studies of the magnetic properties of several metal complexes were also conducted. Magnetic susceptibilities of Cu(II) complexes showed that the Cu(II) are paramagnetic. The magnetic moments obtained were consistent with those reported for Cu(II). II The crystal structure of some metal complexes revealed that the Schiff bases always behaved as bidentate ligands which chelated through the azomethine nitrogen and deprotonated sulphur or oxygen. Determination by X-ray diffraction have showed that, in the solid state of the complexes, the bis(1H-Indole-3-carbaldehyde)thiocarbohydrazone and 1H-Indole-3-carbaldehyde thiosemicarbazone exhibit as thiol tautomer while bis(1H-Indole-3-carbaldehyde)carbohydrazone existed as an enol tautomer. The crystal structure showed that the NiInd3Thio possessed self assembly via the hydrogen bonds to furnish infinite layer structure. Besides, the structure for bis(1H-Indole-3-carbaldehyde)carbohydrazone formed infinite zigzag chain structure due to hydrogen bonds between the independent molecules. The toxicity study and antiulcerogenic activity were carried out. The metal complexes have showed significantly property in preventing the ulcer disease especially for the Zn(II) and Cd(II) complexes.